Postoperative Complications of True Dropless Cataract Surgery versus Standard Topical Drops - Wotipka, Evan K.; Wright, Alex J.; Fan, James Z.; Fuhriman, David; Chuang, Alice Z.; Lindhorst, Grace C.; Feldman, Robert M.; Crowell, Eric L. (Journal of Academic Ophthalmology, 2023)
Purpose Compare postoperative outcomes in cataract surgery between eyes with standard drop regimen versus dropless protocol by residents.Design Retrospective cohort study between April 1, 2018 and March 31, 2020.Methods The study was performed at Lyndon B. Johnson General Hospital in Houston, Harris County, Texas. A total of 547 eyes (234 dropless vs. 313 standard) with phacoemulsification cataract surgery and minimum of 1-month follow-up with best-corrected visual acuity (BCVA) were included. Dropless received 40 mg sub-Tenon's triamcinolone and intracameral moxifloxacin. Patients were followed at postoperative day 1 (POD1), week 1 (POW1), and month 1 (POM1). Postoperative rate of BCVA better than 20/40 (Good vision) and rate of complications were compared between groups.Results Good vision on POM1 in dropless (77.8%) was noninferior to standard (75.1%, p = 0.80). Complication rate in dropless (28.6%) was noninferior to standard (24.0%, p = 0.13). Intraocular pressure (IOP) elevation on POD1 (p = 0.041) and anterior chamber (AC) cells on POW1 and POM1 (p < 0.001) were more frequent in dropless. Mean spherical equivalent at POM1 was better in dropless (−0.37 D [±0.81 D]) compared with standard (−0.61D [±0.77 D], p = 0.001). Early posterior capsular opacification (early PCO) was more frequent in dropless (p = 0.042).Conclusions Postoperative rate of BCVA better than 20/40 and rate of postoperative complications were noninferior, although dropless had higher rates of AC inflammation, IOP elevation, and early PCO.
Keywords: dropless; cataract surgery; resident